Pembuatan Biodiesel Dari Minyak Goreng Bekas (Jelantah) Menggunakan Reaktor Menbran (Variasi Rasio Molar Umpan Dan Konsentrasi Katalis) (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Membrane reactor is an alternative technology that is used in the manufacture of biodiesel, one of the advantages that the reaction and separation process takes place in a single stage simultaneous. This research aims to study the effect of the variation of the catalyst and mole ratio feed waste cooking oil- methanol in biodiesel production, transesterification process which was held in a membrane reactor with a variation of the mole ratio of waste cooking oil - methanol 1:12, 1:16, and 1:20, the concentration of the base catalyst 1% -wt, 1.5% -wt and 2% -wt, pressure transmembrane 2 bar and a temperature of 60 oC process. The results showed biodiesel production using membrane reactor reached 94.81% yield on the condition of the mole ratio of 1:16 with a concentration of 2 %-wt, characteristics of biodiesel produced meets the quality standards of biodiesel in Indonesia including biodiesel, densityis 850-873 kg/m3, viscosity cinematic of biodiesel 5.12-5.97 mm2/s, Flash Point 150-160 Â°C, Acid Number 0.55 to 0.64 mg-KOH/g.Keywords: biodiesel, waste cooking oil, membrane reactor, mol ratio, catalyst concentration.